Slit system partial closure simulation in a stringer reinforced perforated isotropic medium - Mir-Salim-zade, M.V. (Проблеми машинобудування, 2018)
On the basis of the methods of the theory of elasticity, a mathematical description of the model of partial closure of a system of slits in a perforated isotropic medium with foreign transverse inclusions is given. На основі методів теорії пружності проведено математичний опис моделі часткового закриття системи щілин у перфорованому ізотропному середовищі зі сторонніми поперечними включеннями. На основе методов теории упругости проведено математическое описание модели частичного закрытия системы щелей в перфорированной изотропной среде с инородными поперечными включениями.